Peningkatan Pengetahuan dan Keterampilan Warga Desa Babakan melalui Pelatihan Pembuatan Cookies Spirulina - Setyaningsih, Iriani; Tarman, Kustiariyah; Hardiningtyas, Safrina Dyah; Pari, Rizfi Faris; Desniar; Uju, Uju; Ramadhan, Wahyu; Nurhayati, Tati (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Cookies are dry cakes made with flour as the primary baking ingredient. Spirulina platensis was rich in protein, amino acids, glycoproteins, essential fatty acids, polysaccharides, and beta-carotene. Therefore, using sago flour combined with spirulina and seaweed in cookies can increase the nutritional value and produce gluten-free cakes. This training aims to increase knowledge about spirulina, packaging, and product marketing strategies and the skills of Babakan village residents by providing training on making spirulina cookies. This community service activity was conducted by counseling and training on making spirulina cookies in Babakan Village, Dramaga. Counseling activities were carried out to increase knowledge about the potential of spirulina, good packaging, and product marketing strategies, as well as training on making spirulina cookies to improve the skills of Babakan village residents. There were 18 training participants: Family Welfare Empowerment administrators and members. Pre-tests and post-tests were carried out before and after the training activities regarding the topic provided by the speakers. The achievements of the training activities were seen from an increase in post-test results, which was 60% answered correctly compared to only 40% for the pre-test. The evaluation results of the participant's acceptance of training topics and training speakers had an average of 58 to 69%, respectively, perfect. While the participants's assessment of the training facilities and consumption had an average of 50%, they were good.